Determinan Partisipasi Wakaf Tunai dalam Perspektif Millenial - Waliyuddinsyah, Muh. Noval; Muid, Muhamad Abdul; Umam, M. Khoirul (Universitas Islam Internasional Darullughah Wadda'wah, 2023)
Cash waqf is an innovation made to make it easier for people to pay waqf. This study aims to identify and analyze the factors that influence the intention to pay cash waqf. This research design with a quantitative approach. The data used is primary data, data collected by distributing questionnaires to 55 respondents. Then the analytical method used is the SEM model to see the relationship of the factors used on the intention to pay cash waqf. The software used is SmartPLS 4. The analysis carried out is validity, reliability, the relationship between the variable x and variable y before entering the moderating variable, and the relationship between the variable x and y in the presence of a moderating variable. The results of this study indicate that attitudes, subjective norms, and religiosity have a significant effect on the intention to pay cash waqf. While knowledge is not significant to the intention to pay waqf. And accountability does not moderate religiosity and knowledge of the intention to pay cash waqf.